Symptoms and objective signs of peripheral sensory neuropathy in POTS and correlations to gastrointestinal symptoms - Linnéa Ekman; Hanna Tufvesson; Elisabet Englund; Lars B. Dahlin; Bodil Ohlsson (PLoS ONE, 2025)
Aim Postural orthostatic tachycardia syndrome (POTS) is a disorder with cardiovascular autonomic dysfunction where multiple and variable symptoms are common, including those from the peripheral and enteric nervous systems. We aimed to investigate subjective and objective signs of small and large fiber neuropathy in a Swedish POTS cohort compared with healthy controls. Secondly, we wanted to examine potential associations between gastrointestinal symptoms and neuropathy signs in POTS. Methods Forty-three patients with POTS (93% female) and 54 healthy controls (76% female) were included in the study. All participants completed a questionnaire including modified neuropathy symptoms score (NSS) and irritable bowel syndrome severity scoring system (IBS-SSS) for gastrointestinal evaluation. Small nerve fibers were investigated by assessing the intraepidermal nerve fiber density (IENFD). Large nerve fiber function was examined through pinprick and vibration perception thresholds (VPTs), using neurothesiometry and multi-frequency vibrometry (MFV). The patients were classified as “High NSS” and “High IBS-SSS” if their total NSS vs. IBS-SSS were above median levels in POTS. Results Peripheral sensory and gastrointestinal symptoms were more prevalent and severe in POTS than in controls. Median VPTs were normal and IENFDs were comparable between POTS and controls (2.26 [1.62–3.08] vs. 1.63 [0.73–2.68] fibers/mm; p = 0.108). The patients with “high NSS” had slightly higher VPTs measured by MFV, although within normal ranges, compared to patients with “low NSS”. The patients within the “high IBS-SSS” group had higher NSS (18.0 [14.3–22.8] vs. 11.0 [4.0–15.0]; p = 0.002) compared to patients with low total IBS-SSS. Conclusion Symptoms of peripheral and enteric neuropathy are common in POTS but no solid evidence was found regarding functional or morphological signs of small or large fiber neuropathy. Neuropathic and gastrointestinal symptoms were closely associated within POTS.